2015
DOI: 10.1002/jssc.201401234
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of three herbicides in wheat, wheat straw, and soil using a quick, easy, cheap, effective, rugged, and safe method with ultra high performance liquid chromatography and tandem mass spectrometry

Abstract: In this study, a sensitive and effective analytical method for the extraction and detection of three herbicide residues (florasulam, fluroxypyr, and halauxifen-methyl) in wheat and soil was developed. Samples were extracted with acetonitrile/water followed by salting out, dispersive solid-phase extraction cleanup, and detection using ultra high performance liquid chromatography coupled with tandem mass spectrometry. The target analytes were detected within a 5 min runtime using an ultra high performance liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…The parent ion of ABM was 895.46 m/z and the quantification ion was 183.04 m/z, and the confirmatory ion was 327.09 m/z. The cone voltages and collision energies of the quantification ion and confirmatory ion were 2 V and 54 V, respectively [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…The parent ion of ABM was 895.46 m/z and the quantification ion was 183.04 m/z, and the confirmatory ion was 327.09 m/z. The cone voltages and collision energies of the quantification ion and confirmatory ion were 2 V and 54 V, respectively [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the Waters Acquity UPLC BEH C18 column (2.1 × 50 mm, 1.7 μm particle size) was first selected. In the positive ESI mode, the use of an acidic mobile phase is conducive to protonate the target compound and can improve the response and peak shape . Therefore, we compared water to 0.2% v/v FA aqueous solution for the aqueous phase, and found that the 0.2% v/v FA aqueous solution was better than water for improving response.…”
Section: Resultsmentioning
confidence: 99%
“…After the widespread acceptance and application of the QuEChERS method , acetonitrile has become largely used to extract pesticide residues from agricultural and environmental matrices . Acetonitrile was shown to be the most advantageous solvent for extraction of pesticide residues from food samples and ethyl acetate was reported to be the second best .…”
Section: Resultsmentioning
confidence: 99%